Desain Media Pembelajaran “Tata Surya 3D” Berbasis Qreatif Educative dengan Fitur Puzzle dan Kuis Interaktif untuk Siswa Kelas VI Sekolah Dasar (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2026)
Students often have difficulty understanding the Solar System material given in elementary school science lessons using only conventional methods due to its abstract nature. This study creates and explains the advantages of "3D Solar System" learning materials with interactive puzzles and quizzes for sixth-grade elementary school students using the Qreatif Educative platform. Qualitative research methodology is applied to this type of library research. Scientific articles from the DOAJ and Google Scholar databases are scanned to collect data. After that, content analysis methods such as data reduction, classification, theory synthesis, and drawing conclusions are applied in this paper. The results of this study, the use of 3D media significantly increases students' cognitive interest and understanding because it provides more realistic and detailed visuals compared to 2D media. Qreatif Educative's interactive puzzle and quiz elements have successfully created a fun and engaging learning environment based on the psychological characteristics of elementary school children who like to learn through play. The conclusion of this study is that the "3D Solar System" media is worth considering as a creative alternative to improve the standard of science teaching and make it more interactive and student-centered.